Epistasis between the MHC and the RCAα block in primary Sjögren syndrome. Issue 6 (18th September 2007) - Lester, S; McLure, C; Williamson, J; Bardy, P; Rischmueller, M; Dawkins, R L
Abstract : Objective: The RCAα block (R egulators of C omplement A ctivation, 1q32) contains critical complement regulatory genes such as CR1 and MCP. This study examined RCAα block haplotype associations with both disease susceptibility and diversification of the anti-Ro/La autoantibody response in primary Sjögren syndrome (pSS). Methods: 115 patients with pSS and 98 controls were included in the study. 93 of 109 (85%) of the patients with pSS were seropositive for Ro/La autoantibodies. The Genomic Matching Technique (GMT) was used to define RCAα block ancestral haplotypes (AH). Results: RCAα block haplotypes, AH1 and AH3, were both associated with autoantibody-positive pSS (p = 0.0003). Autoantibody associations with both HLA DR3 and DR15 have been previously defined. There was an epistatic interaction (p = 0.023) between RCAα AH1 and HLA DR3, and this genotypic combination was present in 48% of autoantibody-positive patients with pSS compared with 8% of controls. This epistasis is most simply attributable to an interaction between C4 and its receptor, CR1, encoded within the RCAα block. Both DR3 and a relative C4 deficiency are carried on the major histocompatibility complex 8.1 ancestral haplotype. Only four of 92 (4%) autoantibody-positive patients with pSS did not carry any risk RCAα or HLA haplotype, compared with 36 of 96 (38%) controls, and there were differences in haplotype frequencies within autoantibody subsets of pSS. Conclusions: Normal population variation in the RCAα block, in addition to the major histocompatibility complex, contributes genetic susceptibility to systemic autoimmune disease and the autoantibody response. This finding provides evidence for the role of regulation of complement activation in disease pathogenesis.